PENILAIAN PRESTASI KERJA: PENGARUH KOMITMEN ORGANISASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI - Futhna Fadlilah; M Trihudiyatmanto (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2023)
Evaluation of employee performance is one of the benchmarks for employee performance. Field data obtained values from 2018-2020 there was an insignificant increase. Several indicators show values in the range of 79.00 to 81.42 indicating employee performance is in the good category. The Employee Performance Target Score (SKP) as a whole is in the range of 78.13 to 79.18, this value indicates that the average performance of employees of the Wonosobo District Civil Service Agency is in the sufficient category.The purpose of this study was to identify the effect of organizational commitment and organizational culture on employee performance through employee performance appraisal (SKP) as a mediating variable.This study uses quantitative methods with primary and secondary data sources. The population used was 27 people, namely all ASN BKD Wonosobo Regency. Data analysis used Smart-PLS, and data collection techniques used questionnaires.The results of this study indicate that organizational commitment and organizational culture have no effect on employee performance, performance appraisal does not mediate the effect of organizational commitment on employee performance, organizational culture influences employee performance appraisal, employee performance appraisal is able to mediate organizational culture on employee performance, and employee performance appraisal affects employee performance.For the future research agenda to be able to develop with other methods, for example by in-depth interviews with respondents so that the data obtained is more in-depth.